FACTORS AFFECTING SOCIAL PARTICIPATION OF ELDERLY PEOPLE: A STUDY IN LAHORE - K. Ahmad; M. Hafeez (Journal of Animal and Plant Sciences, 2011)
Social participation is deemed to have strong bearing on the health and life quality of older people. The objective of the present study was to identify major factors associated with social participation of older people. The data for the present paper draws from the survey carried out in 2006 on management of chronic conditions and healthy ageing. The findings of the present study indicated that the older individuals’ social participation was significantly associated with their socio-economic positions, presence of severely limiting chronic conditions, widowhood status and gender. Chronological age is largely attributed to the reduced participation in social life. However, we found that socio-economic status and gender of the respondents were significant factors in determining the social participation of the older people.
Keywords: Ageing; Chronic Conditions; social participation; spouse.